Pengaruh Pemberian Susu Tinggi Protein terhadap Tingkat Nafsu Makan dan Kadar Glukosa Postprandial - Harna Harna; Clara M.Kusharto; Katrin Roosita; Andi Muh Asrul Irawan (Media Kesehatan Masyarakat Indonesia, 2018)
High protein milk is a complex food that contains several potential bioactive compounds that might effecton appetite control. However, the mechanism of high protein milk effect on appetite is still poorly understood inunderweight adults. This study aimed to analyze the effect of high protein milk on appetite level and postprandialglucose. This study used experimental trial with design randomized controlled trial. The subjects were divided intotwo groups, 24 subjects in the treatment group and 23 subjects in the control group. Treatment group was givenhigh protein milk and control group was given glucose. Subjective feelings including hunger, satisfaction, anddesire to eat were evaluated using Visual Analogue Scale (VAS), which is analyzed in the incremental Area Underthe Curve (iAUC). The results showed that there was a significant increase in iAUC value of hunger level in thetreatment group compared with control (p<0.05), 8881±638.4 min.mm treatment group and 7297.8±439.6 min.mm control group. There was no significant difference in the level of satisfaction and desire to eat between the twogroups (p>0.05). Postprandial glucose levels in the treatment group were significantly (p<0.05) lower than thecontrol group. The study concluded that high protein milk intervention was increase hunger levels in underweightadults.